Direct detection of gas-phase mercuric chloride by ion drift - Chemical ionization mass spectrometry. (1st October 2020) - Khalizov, Alexei F.; Guzman, Francisco J.; Cooper, Matthew; Mao, Na; Antley, John; Bozzelli, Joseph
Abstract: Mercury is a persistent environmental pollutant that enters the atmosphere mostly in elemental form (Hg 0 ) and leaves in oxidized form. The atmospheric oxidation mechanism of Hg 0 is inadequately constrained because of the limited direct experimental knowledge of molecular identities of gaseous oxidized mercury (GOM), severely hindering the evaluation of mercury deposition to the terrestrial and aqueous environment. Here we present the development and testing of a direct approach for laboratory detection of GOM, using the ion drift - chemical ionization mass spectrometry (ID-CIMS). In this approach, GOM reacts in an ion drift tube with an appropriate reagent ion to form well-defined product ions, which are detected by a quadrupole mass spectrometer equipped with a counting electron multiplier. We used HgCl2 as GOM surrogate, along with SF6 −, CO3 −, and NO3 − ⋅HNO3 as reagent ions, which were selected based on quantum chemical evaluations of several possible reaction mechanisms, including charge transfer, ion transfer, and ion-molecule clustering. All three reagent ions react with HgCl2 through one or more of the above mechanisms, providing a sensitivity sufficient for laboratory studies of atmospheric mercury chemistry. To make direct sampling of atmospheric GOM possible, the sensitivity must be improved, primarily through the use of the ambient pressure chemical ionization. Graphical abstract: Image 1 Highlights: Chemical ionization mass spectrometry can be used for detection of oxidized mercury. Ionization occurs by electron transfer, ligand transfer, or clustering. The sensitivity is sufficient for laboratory studies of mercury chemistry. The sensitivity can be improved for detection of atmospheric oxidized mercury.